Intersection Of Conflicting Interests In The Ottoman Borderlands: The Sanasarian School Of Erzurum In Russian Consular Reports On The Eve Of The Great War - Gazdik, Daniel (ՀՀ ԳԱԱ)
This study examines the Sanasarian School of Erzurum as a contested site in Russian-Ottoman imperial rivalries on the eve of the Great War. Using Russian consular reports, it explores how the school became a focal point of geopolitical struggles, caught between Armenian national aspirations and foreign influences. Founded in 1881, the Sanasarian School was a prestigious Armenian institution, yet Russian authorities viewed it with suspicion, fearing its role in fostering nationalist sentiment and the Armenian Revolutionary Federation influence. The school’s strategic location made it a nexus of competing Russian, Ottoman, and German interests, reflecting broader power struggles in the region. This paper argues that the school was not merely a passive recipient of imperial policies but an active participant in transimperial networks, demonstrating how education shaped identity, political activism, and great-power intervention in the contested Ottoman borderlands.
Keywords: Erzurum; Ottoman Empire